Method for improving inclusion capacity of lanthanum oxide in borosilicate glass solidified body
By using CaO instead of Li2O in borosilicate glass and optimizing the glass network structure, the problem of insufficient La2O3 packaging capacity was solved, and efficient inclusion and stable solidification of La2O3 in borosilicate glass were achieved, thereby improving the uniformity and chemical stability of the glass.
Patent Information
- Application Number
- CN202511082047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-10-17
AI Technical Summary
The existing borosilicate glass has insufficient La2O3 encapsulation capacity, resulting in poor glass uniformity and chemical stability, which affects the deep geological disposal of high-level radioactive liquid waste.
CaO is used instead of Li2O as an additive in borosilicate glass to optimize the glass network structure. The low charge density and large ionic radius of Ca2+ can reduce the attraction of non-bridging oxygen and improve the solubility and packaging capacity of La2O3.
The encapsulation capacity of La2O3 in borosilicate glass has been significantly improved, the uniformity and chemical stability of the glass have been enhanced, and the relevant standards of the nuclear industry have been met.
Smart Images

Figure CN120794346A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-level radioactive liquid waste glass solidification, and particularly relates to a method for increasing the encapsulation capacity of La2O3 in a borosilicate glass solidification body. Background Art
[0002] High-level liquid radioactive waste (HLW) refers to the HLW generated from the reprocessing of spent fuel from the nuclear fuel cycle, its solidified form, and spent fuel destined for direct disposal. It is characterized by high specific activity, high heat release rate, and the presence of radionuclides with long half-lives and high biotoxicity. Therefore, its treatment and disposal technologies are complex, challenging, and expensive, making it a key research and development topic in current radioactive waste management. The most effective approach to disposing of HLW is generally considered to be solidification, followed by final geological disposal of the resulting solidified form. Nuclear vitrification involves mixing nuclear waste with a glass additive, melting it at high temperatures, and casting it into a solidified glass. Radioactive elements are solidified within the glass at the atomic scale, ensuring the safety of its geological storage.
[0003] La2O3 is a rare earth oxide, and its chemical properties are similar to those of key fission products in high-level liquid waste (HLW) (such as Pu 3+ 、Am 3 + 、Cm 3+ Similar to La2O3 (such as La2O3), it has a high charge density and complex coordination behavior, which can easily cause phase separation or crystallization during the glass solidification process, reducing the uniformity and chemical stability of the glass. Therefore, studying the solidification behavior of La2O3 in glass has important guiding significance for the treatment of high-level radioactive liquid waste.
[0004] In the current research on glass solidification of the simulated nuclide La2O3, borosilicate glass has insufficient tolerance for La2O3, with a maximum capacity of 30wt%. Excessive addition will lead to amorphous phase separation or crystalline phase precipitation (such as LaBO3, La2SiO5), affecting the homogeneity of the glass and making it difficult to predict its evolution behavior in deep geological disposal environments. Summary of the Invention
[0005] The object of the present invention is to provide a method for increasing the capacity of La2O3 in a borosilicate glass solid body. The method provided by the present invention increases the solubility of La2O3 in borosilicate glass and significantly improves the capacity of borosilicate glass for La2O3.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for increasing the capacity of La2O3 in a borosilicate glass solid body, comprising the following steps:
[0008] Mixing raw materials for preparing borosilicate glass and La2O3 to obtain a mixture; the raw materials for preparing borosilicate glass are SiO2 powder, boric acid powder, aluminum hydroxide powder and calcium carbonate powder, the mass content of La2O3 in the mixture is > 30% and < 36%;
[0009] Firing the mixture to obtain a glass melt;
[0010] Cooling the glass melt to obtain a borosilicate glass solidified body with solidified La2O3.
[0011] Preferably, the composition of the borosilicate glass includes, in terms of mass content of oxides:
[0012] SiO2 50-56%, B2O3 12-17%, Al2O3 3-6% and CaO 25-26%.
[0013] Preferably, the mass content of La2O3 in the mixture is ≥ 32% and < 36%.
[0014] Preferably, the mass content of La2O3 in the mixture is 34%.
[0015] Preferably, the firing includes the following steps:
[0016] Raising the temperature of the mixture to a first temperature to obtain a molten material; raising the temperature of the molten material to a second temperature after a first holding treatment to obtain an initial glass melt; and performing a second holding treatment on the initial glass melt to obtain the glass melt; the second temperature is 1300-1350°C.
[0017] Preferably, the first temperature is 800-850°C; the first holding treatment is performed for 2-3 hours; and the second holding treatment is performed for 2-3 hours.
[0018] Preferably, the heating rate from room temperature to the first temperature is 5-10°C / min; and the heating rate from the first temperature to the second temperature is 5-10°C / min.
[0019] Preferably, the cooling includes pouring the glass melt on a preheated base for cooling, and the temperature of the preheated base is 400-450°C.
[0020] Preferably, the base is a carbon plate or a steel plate.
[0021] Preferably, the mixing method is grinding.
[0022] The application provides a method for improving the inclusion capacity of La2O3 in borosilicate glass solidification body, comprising the following steps: mixing borosilicate glass preparation raw materials and La2O3 to obtain a mixture; the borosilicate glass preparation raw materials are SiO2 powder, boric acid powder, aluminum hydroxide powder and calcium carbonate powder, the mass content of La2O3 in the mixture is > 30% and < 36%; the mixture is fired to obtain a glass melt; and the glass melt is cooled to obtain a borosilicate glass solidification body containing solidified La2O3. Related technologies use borosilicate glass containing Li2O to solidify La2O3, wherein Li + The high ion charge density can attract non-bridging oxygen (NBO) in the glass, leading to the rupture of Si-O-Si and B-O-B networks in the borosilicate glass structure, generating Si-O - or B-O - (NBO), and the high field strength of Li + can cause local polarization of the glass structure, reduce uniformity, and cause La2O3 to be enriched in local microzones, that is, La 3+ is gathered due to high charge attraction by NBO regions, thereby causing poor uniformity of La2O3 distribution in the glass solidification body and easy leaching. After CaO is used to replace Li2O in the application, because the ionic radius of Ca 2+ is larger than that of Li + , the charge density is lower, the attraction to NBO is smaller, the local distortion of the network structure is reduced, the uniformity of the glass structure is enhanced, and in addition, one Ca 2+ can replace two Li + , and is more efficient in neutralizing the negative charge of [SiO4] - or [BO4] - , thereby reducing the number of NBO and stabilizing the glass network. Therefore, the more uniform and stable glass network structure makes it more difficult for La2O3 to gather. Thus, the silicate glass used in the application replaces Li2O with CaO, reduces the strong field effect of alkali metal ions, optimizes the glass network structure, inhibits the aggregation of La2O3 in the glass solidification body, and improves the solubility of La2O3 in the borosilicate glass, thereby facilitating the improvement of the inclusion capacity of the borosilicate glass for high-level liquid waste (La2O3 can simulate minor actinides). The application facilitates the research on the inclusion capacity of high-level liquid waste (La2O3 can simulate minor actinides) in the glass solidification body by improving the solubility of La2O3.
[0023] Experiments show that the maximum inclusion capacity of La2O3 in lithium-containing borosilicate glass is 30wt%, and the maximum inclusion capacity is increased to 34wt% after CaO replaces Li2O. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1XRD pattern of the solidified Li2O-containing borosilicate glass solidified body solidified La2O3 prepared for the present application comparative example 1.
[0025] Figure 2 XRD pattern of the solidified borosilicate glass solidified body solidified La2O3 prepared for the present application example 1. DETAILED DESCRIPTION
[0026] The present application provides a method for improving the inclusion capacity of La2O3 in a borosilicate glass solidified body, comprising the following steps:
[0027] Mixing the raw materials for preparing the borosilicate glass and La2O3 to obtain a mixture; the raw materials for preparing the borosilicate glass are SiO2 powder, boric acid powder, aluminum hydroxide powder and calcium carbonate powder, the mass content of La2O3 in the mixture is > 30% and < 36%.
[0028] Firing the mixture to obtain a glass melt;
[0029] Cooling the glass melt to obtain a borosilicate glass solidified body solidified La2O3.
[0030] In the present application, all the raw materials / components are commercially available products well known to those skilled in the art, unless otherwise specified.
[0031] The present application mixes the raw materials for preparing the borosilicate glass and La2O3 to obtain a mixture; the raw materials for preparing the borosilicate glass are SiO2 powder, boric acid powder, aluminum hydroxide powder and calcium carbonate powder, the mass content of La2O3 in the mixture is > 30% and < 36%.
[0032] In the present application, the composition of the borosilicate glass preferably includes, in terms of mass content of oxides: SiO2 50-56%, B2O3 12-17%, Al2O3 3-6% and CaO 25-26%.
[0033] In a specific embodiment of the present application, the composition of the borosilicate glass includes, in terms of mass content of oxides: SiO2 powder 54.71%, B2O3 powder 14.96%, Al2O3 powder 4.51% and CaO powder 25.82%.
[0034] The raw materials of the borosilicate glass in the present application are in accordance with the composition of the borosilicate glass.
[0035] The present application uses CaO instead of Li2O in the borosilicate glass, which can improve the inclusion capacity of La2O3 in the borosilicate glass; however, MgO cannot be used instead of Li2O in the borosilicate glass. Since Mg 2+ ions Radius ratio Ca 2+ Ion Small, field strength is higher (charge density between Li + and Ca 2+ ), can partially stabilize network ([SiO4] - or [BO4] - ), but not as Ca 2+ effective, Mg 2+ field strength is higher, the dispersion ability of La 3+ is weak, may attract La 3+ locally, resulting in La2O3 in borosilicate glass solidified body micro area aggregation, affect the borosilicate glass solidified body on the inclusion of La2O3 capacity.
[0036] Meanwhile, the mass content of CaO powder in the borosilicate glass is preferably 25.82%, which can further improve the capacity of borosilicate glass solidified body on La2O3. When the content of CaO in borosilicate glass is too small, the negative charge of glass [BO4] - or [SiO4] - cannot be fully neutralized, resulting in an increase in non-bridging oxygen (NBO) and loose structure. When the content of CaO in borosilicate glass is excessive, the strong aggregation of Ca 2+ will cause the glass to phase separate, resulting in the diffusion of La 3+ being blocked and being forced to be enriched in the micro area of borosilicate glass.
[0037] In the present application, the mass content of La2O3 in the mixture is preferably ≥32% and <36%, and most preferably 34%, which can be 10%, 20%, 30%, 32%, 34% or 36% in the examples.
[0038] In the present application, the mixing method is preferably grinding. The grinding preferably includes grinding in an agate mortar or ball milling in a ball mill. The ball milling is preferably carried out in a planetary ball mill. The mixing temperature is preferably room temperature, and the mixing time is preferably 40-45 min.
[0039] After obtaining the mixture, the present application performs sintering on the mixture to obtain a glass melt. After obtaining the mixture, the present application preferably places the mixture in a corundum crucible, and then performs the sintering. In the present application, the sintering is preferably carried out in a high-temperature box-type resistance furnace. The sintering is preferably carried out under static conditions. The sintering is carried out in an air atmosphere.
[0040] In the present application, the sintering preferably includes the following steps:
[0041] The mixture is heated to a first temperature to obtain a molten material; the molten material is subjected to a first holding treatment and then heated to a second temperature to obtain an initial glass melt; and the initial glass melt is subjected to a second holding treatment to obtain the glass melt. In the present application, the heating rate from room temperature to the first temperature is preferably 5-10℃ / min, and in the examples, it can be 5℃ / min or 10℃ / min. The first temperature is preferably 800-850℃. The first holding treatment is preferably for 2-3h. The heating rate from the first temperature to the second temperature is preferably 5-10℃ / min, and in the examples, it can be 5℃ / min or 10℃ / min. The second temperature is preferably 1300-1350℃. The second holding treatment is preferably for 2-3h.
[0042] In the present application, the sintering does not need to be stirred.
[0043] After obtaining the glass melt, the present application cools the glass melt to obtain a solidified La2O3-containing borosilicate glass solidified body.
[0044] In the present application, the cooling preferably comprises: pouring the glass melt on a preheated base for cooling. The temperature of the preheated base is preferably 400-450℃. The base is preferably a carbon plate or a steel plate. The cooling is preferably cooling to room temperature.
[0045] In order to further illustrate the present application, the technical solutions provided by the present application are described in detail below in conjunction with the examples, but they should not be understood as limiting the scope of protection of the present application.
[0046] Example 1:
[0047] The present example provides a method for increasing the La2O3 content in a borosilicate glass solidified body. In the present example, the composition of the borosilicate glass includes, in terms of mass content of oxides: SiO2 powder 54.71%, B2O3 powder 14.96%, Al2O3 powder 4.51%, and CaO powder 25.82%.
[0048] The method comprises the following steps:
[0049] The raw materials for preparing the borosilicate glass, SiO2 powder, boric acid powder, aluminum hydroxide powder, and calcium carbonate powder, are weighed according to the above glass composition, and then La2O3 is weighed. The mass of La2O3 is 0wt%, 10wt%, 20wt%, 30wt%, 32wt%, 34wt%, 36wt%, and 38wt% of the total mass of the mixture; then the weighed raw materials are ground in an agate mortar for 45min to obtain 30g of a mixture;
[0050] The mixture was transferred into a 100 mL corundum crucible and placed in a high-temperature box-type resistance furnace. By controlling the temperature program, the temperature was raised from room temperature to 850°C at a rate of 10°C / min to obtain a molten material, and the temperature was maintained for 2 hours, then raised to 1300°C at a rate of 10°C / min and maintained for 3 hours, then poured onto a preheated (450°C) carbon plate and cooled to room temperature to obtain a glass solidified body sample, respectively recorded as La0, La10, La20, La30, La32, La34, La36, La38.
[0051] Comparative Example 1:
[0052] The present comparative example provides a preparation method of a borosilicate glass solidified body solidified La2O3, comprising the following steps:
[0053] The raw materials for preparing the borosilicate glass were batched according to SiO2 powder 54.71wt%, B2O3 powder 14.96wt%, Al2O3 powder 4.51wt%, CaO powder 16.82wt% and Li2O powder 9wt%, and then La2O3 was batched, the mass of La2O3 was 0wt%, 10wt%, 20wt%, 30wt%, 32wt%, 34wt% of the total mass of the mixture; then the batched raw materials were placed in an agate mortar and ground for 45 min to obtain a mixture of 30g;
[0054] The mixture was transferred into a 100 mL corundum crucible and placed in a high-temperature box-type resistance furnace. By controlling the temperature program, the temperature was raised from room temperature to 850°C at a rate of 10°C / min to obtain a molten material, and the temperature was maintained for 2 hours, then raised to 1300°C at a rate of 10°C / min and maintained for 3 hours, then poured onto a preheated (450°C) carbon plate and cooled to room temperature to obtain a glass solidified body sample, respectively recorded as LiLa0, LiLa10, LiLa20, LiLa30, LiLa32, LiLa34.
[0055] Test Example:
[0056] (1) The chemical stability of the glass solidified body sample prepared in Example 1 was detected, and the detection results of 28 days are shown in Table 1.
[0057] The calculation method of the leaching rate in Table 1 is as follows:
[0058] The chemical stability of the solidified body was tested according to the MCC-1 static immersion method in the ASTM standard. The obtained solidified body sample was cut into a cube of 10mm×10mm×10mm, and each surface was polished smooth, then ultrasonically cleaned with ionized water and anhydrous ethanol, each for three times. The sample was immersed in the leaching agent (electrical conductivity less than 10.0μS·m-1 The sample was hung in a polytetrafluoroethylene tank with complete immersion of the sample in deionized water with conductivity less than 10.0 μS·m -1 The polytetrafluoroethylene liner was finally placed in a 100 mL reactor, and a constant temperature drying box at 90±1℃ was used as experimental equipment to conduct a 28-day static leaching experiment. The solution obtained by the 28-day leaching experiment was analyzed by inductively coupled plasma optical emission spectrometer (ICP-OES, iCAP-6500 type), and the concentration distribution of Ca, Si and La was determined. The normalized leaching rate LR i of the related elements was calculated using formula (1).
[0059]
[0060] In formula (1), LR i is the normalized leaching rate of element i in the leaching solution, with a unit of g·m -2 ·d -1 ; Ci represents the concentration of element i in the leaching solution, with a unit of g·L -1 ; V is the volume of the leaching solution, L; f i represents the mass percentage of element i in the sample; and S is the total surface area of the sample, with a unit of m 2 ; and Δt is the time required for soaking, with a unit of d.
[0061] Table 1: Normalized leaching rates of Ca, Si and La elements in the glass solidified body sample prepared in Example 1
[0062]
[0063] The chemical stability of the glass solidified body prepared in Example 1 is relatively excellent, and the normalized leaching rates of Ca and Si elements are maintained at 10 -3 g·m -2 ·d -1 , and the content of La element is too low to be measured, until the content reaches 38 wt%, which is 10 -7 g·m -2 ·d -1 , and the glass solidified body prepared in Example 1 exhibits excellent leaching resistance. In Table 1, when the content of La2O3 is 34%, the three elements (Si element, Ca element and La element) respectively meet the condition that the leaching rate is less than 1 g·m -2 ·d -1 , and when the content of La2O3 is 36%, as Figure 2As shown, the part exceeding the inclusion capacity precipitates in the form of CaLa4(SiO4)3O (PDF 71-1368) crystals, but does not reach the detection upper limit of the instrument, indicating that the glass solidified body prepared in Example 1 has a stable chemical structure, can stably solidify La2O3 simulated nuclides, has excellent chemical stability, and meets the relevant standards of the nuclear industry.
[0064] (2) The glass solidified body samples prepared in Example 1 and Comparative Example 1 were subjected to XRD detection. Figure 1 The XRD pattern of the lithium-containing borosilicate glass solidified body prepared in Comparative Example 1 of the present application for solidified La2O3; Figure 2 The XRD pattern of the borosilicate glass solidified body prepared in Example 1 of the present application for solidified La2O3.
[0065] Figure 1 In the present application, a lithium-containing borosilicate glass formula is used, and Figure 2 In the present application, a lithium-containing borosilicate glass formula is used, and 2+ can replace 2 Li + , can more efficiently neutralize the negative charge of [SiO4] - or [BO4] - , thereby stabilizing the glass network. In addition, compared with Li + , Ca 2+ has a lower charge density and is more gentle in attracting NBOs, which can reduce the local distortion of the network structure and increase the uniformity of the glass solidified body.
[0066] Example 2:
[0067] The present embodiment provides a method for improving the inclusion capacity of La2O3 in a borosilicate glass solidified body, comprising the following steps:
[0068] The raw materials for preparing the borosilicate glass are batched according to SiO2 powder 54.71wt%, B2O3 powder 14.96wt%, Al2O3 powder 4.51wt%, and CaO powder 25.82wt%, and then La2O3 is batched, with the mass of La2O3 being 34wt% of the total mass of the mixed material; then the batched raw materials are uniformly mixed in a planetary ball mill for 45min to obtain 30g of mixed material;
[0069] The mixture was transferred into a 100 mL corundum crucible and placed in a high-temperature box-type resistance furnace. By controlling the temperature rising program, the temperature was raised from room temperature to 850℃ at a rate of 10℃ / min to obtain a molten material, and then the temperature was kept for 2 hours, and then raised to 1300℃ at a rate of 10℃ / min and kept for 3 hours, and then poured on a preheated (450℃) carbon plate to cool to room temperature to obtain a glass solidified body sample.
[0070] Example 3:
[0071] The present example provides a method for improving the inclusion amount of La2O3 in a borosilicate glass solidified body, comprising the following steps:
[0072] The raw materials for preparing the borosilicate glass were batched according to SiO2 powder 54.71wt%, B2O3 powder 14.96wt%, Al2O3 powder 4.51wt%, and CaO powder 25.82wt%, and then La2O3 was batched, the mass of La2O3 being batched according to 34wt% of La2O3 based on the total mass of the mixture; then the batched raw materials were mixed in a planetary ball mill for 45min to obtain a mixture of 30g;
[0073] The mixture was transferred into a 100 mL corundum crucible and placed in a high-temperature box-type resistance furnace. By controlling the temperature rising program, the temperature was raised from room temperature to 850℃ at a rate of 5℃ / min to obtain a molten material, and then the temperature was kept for 2 hours, and then raised to 1300℃ at a rate of 5℃ / min and kept for 3 hours, and then poured on a preheated (450℃) steel plate to cool to room temperature to obtain a glass solidified body sample.
[0074] Example 4:
[0075] The present example provides a method for improving the inclusion amount of La2O3 in a borosilicate glass solidified body, comprising the following steps:
[0076] The raw materials for preparing the borosilicate glass were batched according to SiO2 powder 54.71wt%, B2O3 powder 14.96wt%, Al2O3 powder 4.51wt%, and CaO powder 25.82wt%, and then La2O3 was batched, the mass of La2O3 being batched according to 34wt% of La2O3 based on the total mass of the mixture; then the batched raw materials were mixed in a planetary ball mill for 45min to obtain a mixture of 30g;
[0077] The mixture was transferred into a 100 mL corundum crucible and placed in a high-temperature box resistance furnace. By controlling the temperature rising program, the temperature was raised from room temperature to 800 DEG C at a rate of 10 DEG C / min to obtain a molten material, and then the temperature was raised to 1300 DEG C at a rate of 10 DEG C / min for 3 hours, and then the molten material was poured on a preheated (450 DEG C) steel plate to cool to room temperature to obtain a glass solidified body sample.
[0078] The leaching rate test results and XRD test results of examples 2-4 are basically the same as the results when the La2O3 accounts for 34wt% of the total mass of the mixture in example 1.
[0079] From the above examples, it can be seen that the application replaces Li2O with CaO, changes the basic borosilicate glass formula, increases the inclusion amount of La2O3 in the borosilicate glass, and the sintering method of the solidified body is simple, which only needs to initially mix the basic glass formula with the simulated nuclide directly, and does not need to stir and mix uniformly in the sintering process.
[0080] Although the above examples make a detailed description of the application, it is only a part of the embodiments of the application, not all the embodiments, and other embodiments can be obtained according to the embodiments without creativity, which all belong to the protection scope of the application.
Claims
1. A method for increasing the capacity of La2O3 in a borosilicate glass solid body, characterized in that: The following steps are involved: Mixing raw materials for preparing borosilicate glass and La2O3 to obtain a mixture; the raw materials for preparing borosilicate glass are SiO2 powder, boric acid powder, aluminum hydroxide powder and calcium carbonate powder, and the mass content of La2O3 in the mixture is greater than 30% and less than 36%; firing the mixture to obtain a glass melt; The glass melt is cooled to obtain a solidified borosilicate glass body containing solidified La2O3.
2. The method for increasing the capacity of La2O3 in a borosilicate glass solidified body according to claim 1, characterized in that: Measured by mass content of oxides, the composition of the borosilicate glass includes: SiO2 50~56%, B2O3 12~17%, Al2O3 3~6% and CaO 25~26%.
3. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 1 or 2, characterized in that: The mass content of La2O3 in the mixture is ≥32% and <36%.
4. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 3, wherein: The mass content of La2O3 in the mixture is 34%.
5. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 1, wherein: The firing comprises the following steps: The mixed material is heated to a first temperature to obtain a molten material; the molten material is subjected to a first insulation treatment and then heated to a second temperature to obtain an initial glass melt; the initial glass melt is subjected to a second insulation treatment to obtain the glass melt; the second temperature is 1300-1350°C.
6. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 5, wherein: The first temperature is 800-850° C.; the first heat preservation treatment time is 2-3 hours; and the second heat preservation treatment time is 2-3 hours.
7. The method for increasing the capacity of La2O3 in a borosilicate glass solidified body according to claim 5 or 6, characterized in that: The heating rate from room temperature to the first temperature is 5-10°C / min; the heating rate from the first temperature to the second temperature is 5-10°C / min.
8. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 1, wherein: The cooling comprises: pouring the glass melt onto a preheated substrate and cooling the preheated substrate, wherein the temperature of the preheated substrate is 400-450°C.
9. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 8, wherein: The substrate is a carbon plate or a steel plate.
10. The method for increasing the La2O3 content in a borosilicate glass solidified body according to claim 1, wherein: The mixing method is grinding.